Hyperuricemia is associated with metabolic syndrome in the community very elderly in Chengdu - Gang Huang (Nature Portfolio, 2020)
Abstract Hyperuricemia is a risk factor for cardiovascular metabolic diseases. However, in the very elderly, the relationship between hyperuricemia and the metabolic syndrome (MetS) is not yet clear. This study was aimed to investigate the potential association between hyperuricemia and MetS in community very elderly in Chengdu. In this cross-sectional study, 1056 very elderly in the community were enrolled. Serum uric acid (SUA), fast plasma glucose, triglycerides and high–density lipoprotein cholesterol were measured, and then MetS components were calculated. Logistic regression models were used to explore risk factors for MetS in the very elderly. Finally, 1035 participants were included in analysis whose ages ranged between 80 and 100 with a mean age of 83.6 ± 3.4 years. The mean SUA level was 356.2 ± 95.0 µmol/L. The estimated prevalence of MetS in the very elderly was 25.0% vs. 21.6% (international diabetes federation (IDF) criteria vs. Chinese guideline), which was significantly higher for women (IDF criteria:17.3% in men vs 33.6% in women, p < 0.001). Logistic regression has found that participants with hyperuricemia (SUA level > 416 µmol/L in men and > 357 µmol/L in women) had a higher risk (IDF criteria: odds ratio (OR): 2.136, 95% confidence interval(CI): 1.525–2.993, p < 0.001. Chinese guideline: OR: 1.769, 95%CI: 1.249–2.503, p = 0.001) of MetS in very elderly Chinese. MetS is common in the community of very elderly Chinese in Chengdu. Hyperuricemia is associated with MetS in general very elderly and lifestyle changing should also be considered in the very elderly.